Caracterización de Alternativas Ecoturísticas en la Hacienda la Nueva Esperanza, Barrio Colcas, Parroquia de Mulalo, cantón Latacunga, provincia de Cotopaxi. - Calixto Mejía, María Gabriela (2019)
The present research Project was focused on identifying the resources that the study site has; where each resource is part of one of the characterized ecotourism alternatives, which can be carried out within the La Nueva Esperanza estate; for that a diagnosis was made which allowed to know and identify the natural and cultural resources that the place has, through the research in primary and secondary sources; and in that way, to determine and characterize each one of them through a technical file and with this, 10 ecotourism alternatives were found and thus be able to zoning the possible activities to be carried out such as the gastronomic workshops, environmental education workshops, cultural photography, planting and harvesting of vegetables, bird watching, nature photographic, interpretive hiking, recreational fishing, horseback riding and finally milking cows. The previous ones could be developed in an extension of 15.71 ha, which are distributed by sectors and according to the space that they could occupy, this project will directly benefit the owner of the Estate and indirectly the whole population of the Colcas neighborhood; resulting; in the social aspect because it can generate jobs when it will be implemented, in the same way in the environmental and economic part that will allow to take advantage of natural and cultural resources to thereby generate economic items when the activity will be developed. In order to determine the areas, a zoning was developed, thus defining the most suitable extension for each alternative, where it was divided into four sectors, which were called with a specific name; sector 1 (The charm) which is named for its lagoon and the beauty of native plants, sector 2 (The Triangle) is called this because at one of its ends a triangle is formed where the grass develops as nowhere else, sector 3 (The Miracle) is called that because it is an area where much water is no need in order to have a good grass development and sector 4 (George) named in honor of the creator of this place since this sector was the most appreciated by him.